A new sociolinguistic taxonomy, 'cookbook', and immigrant communities - Asahi, Yoshiyuki (Slavia Centralis, 2020)
This paper proposes a sociolinguistic taxonomy, called 'cookbook', which aims to account for highly diverse communities. The definition of this 'cookbook' was derived based on its literal meaning, its usage in laboratory situations. 'Cookbook' aims to categorise both the speaker at a micro level and society at a macro level at the same time. This will enable us to render more accurate sociolinguistic descriptions in a given community. As examples, two case studies (new town study and diaspora study) are introduced to show how 'cookbook' can explain the attested linguistic variation.
Keywords: ‘cookbook’; sociolinguistic taxonomy; language variation; Japanese; new town; diaspora